The Study of Local Government Policy and its Impact on Public Satisfaction and Incumbent Electability: An Analysis of Experiences from Jambi Province - Pahrudin HM; Hatta Abdi Muhammad; Burlian Senjaya; Samia Elviria; Zakly Hanafi Ahmad; Syafrial Syafrial; Salman Salman (Journal Public Policy, 2026)
Studies on Indonesian local elections have covered identity politics, patronage, and candidate charisma in great detail, but they don't provide much empirical data on how actual policy performance affects public satisfaction and incumbent electability at the province level. There is a research gap regarding whether policy-driven satisfaction quantitatively translates into voter support, especially in decentralized regions where visibility and impact of government programs vary significantly. This is because scholars have rarely integrated public service satisfaction metrics with electoral behavior. By examining whether local government policy effectiveness directly affects satisfaction levels and, in turn, determines incumbent electability in Jambi Province, this study closes that gap. 880 respondents were chosen for this quantitative survey study utilizing a multistage random sampling procedure with a 4% margin of error, and SPSS was used for analysis. The results show that a number of development initiatives, most notably the Dumisake Program, were carried out under the Haris–Sani administration (2020–2024) and received strong public support. While electability data reveals that 51.50% of respondents planned to vote for Haris-Sani in the 2024 Governor Election, the Community Satisfaction Index (IKM) reveals that 60.40% of respondents were satisfied with the administration's plans. The official election result, in which Haris-Sani easily defeated Romi-Sudirman and was subsequently appointed for the 2025–2030 term, clearly represented these opinions. The study finds that increased public satisfaction with local government programs significantly and favorably affects the incumbent's electability, indicating that policy performance continues to be a crucial factor in determining voter behavior in regional elections.